Rights Offerings, Subscription Period, Shareholder Takeup, and Liquidity - Balachandran, Balasingham; Faff, Robert; Theobald, Michael; van Zijl, Tony (Journal of Financial and Quantitative Analysis, 2012)
We examine the role of shareholder takeup in rights offerings on the subscription period price reaction and liquidity. Our results indicate that takeup information is reflected in price adjustments over the subscription period and that quality-related information disclosed on the rights announcement date further impacts prices in this period. Higher shareholder takeup improves liquidity. We do find some evidence of inefficiencies in the adjustment process over the subscription period that, in part, is consistent with a model where markets are characterized by overconfident investors and that also articulates with takeup information arriving in the market.